Re-thinking HIV-Related Stigma in Health Care Settings: A Qualitative Study - Gagnon, Marilou (Journal of the Association of Nurses in AIDS Care, 2015)
People living with HIV (PLWH) continue to endure stigma and discrimination in the context of health care. This paper presents the findings of a qualitative study designed to (a) describe stigmatizing and discriminatory practices in health care settings, and (b) explore both symbolic and structural stigma from the perspectives of PLWH. For the purpose of this qualitative study, 21 semi-structured in-depth interviews were conducted in the province of Quebec, Canada. The data were analyzed following the principles of thematic analysis. During analysis, three themes were identified, and relations between these themes were delineated to reflect the experiences of participants. The findings suggest that HIV-related stigma in health care settings is episodic in nature. The findings also suggest that HIV-related stigma is experienced through interactions with health care providers (symbolic stigma) and, finally, that it is applied systematically to manage risk in the context of health care (structural stigma).
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; inégalités; justice sociale; premier cycle; périodes historiques; québec; régions géographiques; santé; sciences humaines; systèmes d'oppressions; thématiques; travail social; trs1205

It's in Our Blood: Indigenous women's knowledge as a critical path to women's well-being - Gaudet, Janice Cindy; Caron-Bourbonnais, Diane (AlterNative: An International Journal of Indigenous Peoples, 2015)
The research reported in this article sought to shed light on the North, Central and South American indigenous moon time teachings related to the menstrual cycle of women. The historical institutionalization, medicalization and colonization of indigenous women's practices have devalued and almost destroyed this knowledge. This study explored the question of whether or not lost indigenous knowledge of women's power can be reclaimed for women's health and well-being. A qualitative participatory research methodology was adopted, based on an indigenous paradigm and scholarly rigour and including protocols acceptable to an Ojibwe grandmother, Isabelle Meawasige, who shared her knowledge and experience. The experiential knowledge gained and the meanings expressed by female participants in a circle sharing facilitated by the principal author are presented and discussed. The results of this research reveal optimistic possibilities to co-create health and well-being for the participants, grounded in what is both visible and invisible within indigenous women's culture.
Keywords: amériques; approches et analyses; care; cours; cycle menstruel; discipline; féminisme autochtone; justice reproductive; médecine; médicalisation; pol4105; premier cycle; règles; régions géographiques; santé; sciences; sciences de la santé; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail social